2014
DOI: 10.30843/nzpp.2014.67.5729
|View full text |Cite
|
Sign up to set email alerts
|

Soil residual activity and plantback periods for the herbicides saflufenacil and topramezone

Abstract: To quantify soil residual activity and plantback periods for two maize herbicides saflufenacil and topramezone different rates were applied to a cultivated soil and samples (05 cm) collected at regular intervals for glasshouse bioassays Phytotoxic residues of saflufenacil applied at 17 g ai/ha the rate used for conservation tillage and pasture renovation persisted in the soil for lt; 2 weeks for the susceptible species viz white clover onion carrot and radish Residual activity from 102 g ai/ha the rate recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 6 publications
2
18
1
Order By: Relevance
“…Topramezone did not significantly reduce visual estimates of cover or NDVI values when hybrid bermudagrass was sprigged 0 WAA, which supports previous reports of limited soil residual activity (Rahman et al, 2014). Results suggest that topramezone is relatively safe to use for site preparation before sprigging hybrid bermudagrass at any time interval.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Topramezone did not significantly reduce visual estimates of cover or NDVI values when hybrid bermudagrass was sprigged 0 WAA, which supports previous reports of limited soil residual activity (Rahman et al, 2014). Results suggest that topramezone is relatively safe to use for site preparation before sprigging hybrid bermudagrass at any time interval.…”
Section: Discussionsupporting
confidence: 87%
“…Although topramezone has little use as a pre‐emergence herbicide within managed turfgrass scenarios, it has been reported to have limited persistence in soil with an average half‐ life of 14 d (AMVAC Chemical Corp., 2007). However, at rates more than two and four times larger than those applied in the present study (0.10 and 0.20 kg ha −1 ), Rahman et al (2014) reported limited residual activity on peas ( Pisum sativum L.), white clover ( Trifolium repens L.), and radish ( Raphanus sativus L.), with the highest injury observed in white clover, 2 WAT. Topramezone may be a viable tank‐mixing option in combination with other herbicides for postemergence goosegrass and crabgrass control prior to sprigging into fallow or freshly prepared soil.…”
Section: Discussioncontrasting
confidence: 56%
“…At the time of tobacco transplanting in April, the Tifton Bowen Farm had received more than 47 cm of rainfall, while the Dawson USDA–ARS facility received 37 cm. For the benzoylpyrazole herbicide topramezone, peas ( Pisum sativum L.) were injured when planted within 2 wk of application (Rahman et al 2014). Topramezone has a half-life of approximately 14 d (Gorsic et al 2008; Shaner 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In Zambia, herbicide use by smallholder farmers is increasing partly driven by the adoption of conservation agriculture (CA) (Nkhoma et al, 2017). Topramezone and Dicamba studies done have shown that the residual herbicides used for controlling weeds in maize crops can sometimes persist in the soil (Rahman et al, 2014). Despite this, there is little information on the residual effects of Topramezone and Dicamba and how this could affect the principles of conservation and sustainable agriculture.…”
Section: Introductionmentioning
confidence: 99%